Natural Infection by SARS-CoV-2 in Companion Animals: A Review of Case Reports and Current Evidence of Their Role in the Epidemiology of COVID-19 - de Morais, Helio Autran; dos Santos, Andrea Pires; do Nascimento, Naila Cannes; Kmetiuk, Louise Bach; Barbosa, David Soeiro; Brandão, Paulo Eduardo; Guimarães, Ana Marcia Sá; Pettan-Brewer, Christina; Biondo, Alexander Welker (Frontiers in Veterinary Science, 2020)
Severe respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the Coronavirus disease 2019 (COVID-19), is the causative infectious agent of the current pandemic. As researchers and health professionals are still learning the capabilities of this virus, public health concerns arise regarding the zoonotic potential of SARS-CoV-2. With millions of people detected with SARS-CoV-2 worldwide, reports of companion animals possibly infected with the virus started to emerge. Therefore, our aim is to review reported cases of SARS-CoV-2-naturally infected animals, particularly companion pets, shedding light into the role of these animals in the epidemiology of COVID-19.